2018
DOI: 10.1002/adma.201806268
|View full text |Cite
|
Sign up to set email alerts
|

A Surface‐Functionalized Ionovoltaic Device for Probing Ion‐Specific Adsorption at the Solid–Liquid Interface

Abstract: Aqueous ion–solid interfacial interactions at an electric double layer (EDL) are studied in various research fields. However, details of the interactions at the EDL are still not fully understood due to complexity induced from the specific conditions of the solid and liquid parts. Several technical tools for ion–solid interfacial probing are experimentally and practically proposed, but they still show limitations in applicability due to the complicated measurements. Recently, an energy conversion device based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…In this paper, we verified the origins of the natural evaporation-induced electricity generation through the porous zinc oxide (ZnO) film as an electrical resistance-controllable metal oxide platform and studied its mechanisms based on the ionovoltaic effect. The solvothermal-grown ZnO showed a significant level of energy generation (∼0.4 V and ∼20 nA of open circuit voltage ( V oc ) and short circuit current ( I sc ), respectively) continuously over 2 h, which suggested a great potential for generating a high density of electrical energy. The device resistance was tuned by an aluminum (Al)-doping process during the solvothermal growth to induce a voltage drop for the ionovoltaic phenomenon .…”
mentioning
confidence: 82%
“…In this paper, we verified the origins of the natural evaporation-induced electricity generation through the porous zinc oxide (ZnO) film as an electrical resistance-controllable metal oxide platform and studied its mechanisms based on the ionovoltaic effect. The solvothermal-grown ZnO showed a significant level of energy generation (∼0.4 V and ∼20 nA of open circuit voltage ( V oc ) and short circuit current ( I sc ), respectively) continuously over 2 h, which suggested a great potential for generating a high density of electrical energy. The device resistance was tuned by an aluminum (Al)-doping process during the solvothermal growth to induce a voltage drop for the ionovoltaic phenomenon .…”
mentioning
confidence: 82%
“…Ions adsorbed on the solid surface are capable of varying the surface charge density and surface potential, that is, forming strong chemical adsorption with the solid by non-Coulombic interactions such as chemical bonding, hydrogen bonding, hydrophobic bonding, and coordinating complexation, hereby greatly affecting the device performance. For example, a mixed self-assembled monolayer (SAM) of 1H,1H,2H,2H-perfluorooctyltriethoxysilane (PFOTS) with a negative surface potential generates reversed signal, with respect to a SAM of N1-(3-trimethoxysilylpropyl)­diethylenetriamine (T-DETA) with a positive surface potential . This is due to the opposite electrical charge of the adsorbed ions on solid surfaces.…”
Section: Mechanical-to-electric Wegmentioning
confidence: 99%
“…For example, a mixed self-assembled monolayer (SAM) of 1H,1H,2H,2H-perfluorooctyltriethoxysilane (PFOTS) with a negative surface potential generates reversed signal, with respect to a SAM of N1-(3-trimethoxysilylpropyl)diethylenetriamine (T-DETA) with a positive surface potential. 24 This is due to the opposite electrical charge of the adsorbed ions on solid surfaces. The ionic strength in the droplet also plays a vital role at their interface, and more ions in the droplet would significantly improve the capacitor strength and output performance.…”
mentioning
confidence: 99%
“…The electric double layer (EDL) is widely known to describe the interaction between ions and solid surfaces at the liquid/solid interfaces, which lays the foundation of many research areas such as electrochemistry, microfluidics, and colloidal chemistry. Recent studies have shown that modulating the EDL at liquid/solid interfaces with different environmental stimuli can lead to electricity generation, including kinetically induced variation of liquid/solid interfaces, thermal evaporation of water, , and humidity variations. In particular, a number of studies have found that electricity can be generated by different kinetic motions (dropping, waving, or flowing) of water or water droplets on various solid surfaces, including dielectric polymers, ,, inorganic oxides, and carbon nanomaterials. These different mechanical stimuli can change the EDL capacitance or increase the interface charge quantities, leading to the potential differences and electrical current between the two electrodes. For example, the high-voltage triboelectric nanogenerators (TENG) were reported by striking water droplets or waving bulk water on the hydrophobic polymer surfaces. , Similarly, electricity generation was reported by squeezing a water droplet placed between an electrode and a polymer-coated electrode. , Electricity generation was also achieved by dropping or waving water on carbon nanomaterials. , …”
Section: Introductionmentioning
confidence: 99%